Canadian Cities as Social Technologies: An Exploratory Essay - Paquet, Gilles; Wallot, Jean-Pierre (Urban History Review / Revue d'histoire urbaine, 1980)
In order to analyze cities as social technologies, it is necessary to focus on middle-range phenomena. The Polanyi/Akerman framework is used to carry out a meso-analytical survey of Canadian urban history in the 1850-1914 period. The Canadian urban system is seen as marginal to the American system in the same way that the Atlantic and Western regions are marginal to Central Canada. This relationship modifies the expected impact of technological and industrial change on the pattern of urban development.